Paroxysmal abdominalgia as a non-motor wearing off phenomenon in Parkinson’s disease. A case series and literature review - Abdalmalik Bin Khunayfir; Stewart A. Factor (Clinical Parkinsonism & Related Disorders, 2025)
Background: Paroxysmal abdominalgia (PxA) is an underrecognized, debilitating form of abdominal pain that manifests during wearing-off (WO) periods in Parkinson’s disease (PD). Despite its profound impact, PxA remains poorly described, complicating diagnosis and management. Methods: We conducted a retrospective case series of patients with PD and recurrent abdominal pain linked to WO episodes. Demographic, clinical, and detailed pain data were extracted from records. Patients with alternative gastrointestinal (GI) causes were excluded. Data were analyzed descriptively and compared with existing literature. Results: Five patients (3 males, mean disease duration 14.4 years) met inclusion criteria. PxA was characterized by severe abdominal pain—described as twisting, squeezing, or tightness—that consistently occurred during WO states and frequently led to emergency department visits and repeated GI evaluations which were unremarkable. Symptoms were often associated with anxiety and panic attacks. Standard analgesics and GI therapies were largely ineffective. Extra carbidopa/levodopa doses provided variable relief; apomorphine bolus injections and continuous subcutaneous foslevodopa/foscarbidopa infusion appeared to offer significant benefit in eligible patients. PxA symptoms aligned best with the nociplastic category of the PD Pain Classification System. Conclusions: PxA is a severe, non-motor complication of PD that likely represents a form of nociplastic pain linked to dopaminergic fluctuations. Increased awareness is needed to reduce misdiagnosis and inappropriate interventions. Further research is required to elucidate underlying mechanisms and guide targeted therapy.